Game over gender, race & violence in video games - Huntemann, Nina; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2000)
This educational documentary offers a refreshing dialogue about the complex and controversial topic of video game violence, and is designed to encourage high school and college students to think critically about the video games they play, instead of dismissing the technology as'harmless fun
Title from title screen
Executive producer, Sut Jhally ; camera, Susan Ericsson ... [et al.] ; editor, Jeremy Smith ; graphics, Jeremy Smith, Ed May ; music, Thom Monahan
Keywords: Video games; Violence; Gender roles; Race